PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA KARANGANYAR - Arinpias Hening Setya; Alwi Suddin; Rahayu Triastity (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
This research was conducted at the Pratama Karanganyar Tax Service Office, the type of data used is qualitative and quantitative data. Data sources used are Pratama and secondary data. The total population in this sample is 124 employees of the Pratama Karanganyar Tax Office. The sample used in this study was taken 40% of the total population of 50 respondents. The sampling technique is done by using proportional cluster random sampling or random sampling in each area in a different section. In this study shows that leadership style does not significantly influence employee performance, while motivation and work discipline significantly influence employee performance.